THEROTICAL PERSPECTIVE OF BABA RAMDEVJI’S ARYUVEDIC FORMULATION AS SUBSTITUTE FOR (SOFT DRINKS) - Dhulia, Ishan; Kush, Dr. Luv (Asian Journal of Pharmaceutical Research and Development, 2013)
Shri Baba Ram Devji once announced in Dainik jagran Newspaper dated August 26, 2006 that he will replace soft drinks by an indigenious ayurvedic drink prepared by the leaves of TULSI, Karela, Kaddu and fruit Kheera possibly following the principle of Rasayana. We do not know what method has been followed in the preparation of such drinks. Our pharmacochemical insight indicated that this ayurvedic or natural product soft drink possesses diverse anticarcinogenic chemical structures. We rationalized the chemopreventive potential of this ayurvedic formulation.